The Governance of the Black Holes of the World Economy: Shadow Banking and Offshore Finance - Ronen Palan; Anastasia Nesvetailova (City, University of London, City Political Economy Research Centre (CITYPERC), 2013)
This paper focuses on regulatory challenges posed by the two interconnected structures of the global financial system – the economy of tax havens (or offshore financial centres), and the shadow banking system. The financial crisis of 2007-09 has revealed that tax havens structures and shadow banking entities play a central role in the practise of financial institutions reliant on financial innovation. Thriving on complexity, opaque networks and driven by arbitrage, the two phenomena pose tremendous challenges to national and international regulators aiming to restore the financial cycle in the recessionary environment. In this paper, we analyse "the state of play" and the current plans for the governance of tax havens, offshore finance and the shadow banking industry. We find that although offshore financial centres and shadow banking are outside the scope of academic economics, they have attracted a lot of attention on the part of financial researchers and regulators. Along with other macro-prudential and system risk concerns, the regulation, or governance of these "black holes" of the global economy is increasingly assuming a central place on the agenda of financial regulators. In what follows, we explore the reasons behind this development.
Keywords: 330